When Context Matters - Application and Potential of Financial Crime Risk Indicators in Selected African Jurisdictions - Marxen, Karl (Potchefstroom Electronic Law Journal, 2022)
This paper explores the application and potential of financial crime risk indicators in the international banking and mercantile transactions. Special emphasis is placed on lists of financial crime risk indicators which are circulated, or have been drafted, by governments and public institutions in Sub-Saharan Africa. This paper investigates, inter alia, whether such financial crime risk indicator lists created by African institutions differ noticeably – regarding content, drafting style, and availability – from other well-established indicator lists, and whether African financial crime risk indicator lists appropriately represent African commercial realities and thus meaningfully contribute to fighting financial crime on the continent and beyond.